Scrotal Skin Metastases Revealing a Prostatic Adenocarcinoma - Idriss Ziani; Zayd El Boukili El Makhoukh; Ahmed Ibrahimi; Omar Bellouki; Jihane Benahmed; Yasmine Laraqui; Fouad Zouidia; Hachem El Sayegh; Lounis Benslimane; Yassine Nouini (Case Reports in Urology)
Introduction. Prostate cancer is the most common cancer in men. Cutaneous metastasis from prostate cancer is an unusual clinical finding. Scrotal skin metastasis revealing a prostate adenocarcinoma is even rarer. Case Report. We report the case of a 78-year-old patient, who initially consulted for nonspecific scrotal skin lesions evolving for 4 months. Patient’s past history revealed urinary disorders. Physical examination and PSA levels led to perform a prostate biopsy, and the diagnosis of prostate adenocarcinoma was made. Bone scintigraphy showed that the cancer has spread to the bones. Imaging studies showed that the cutaneous lesions were limited to the scrotal wall. Cutaneous metastasis was suspected and was proven on skin biopsy. The patient received second-generation hormone therapy with good clinical and biological outcomes. Discussion. Based on literature review of nearly 2,500 skin metastases, we found that only 436 were spreading from the genitourinary tract. Skin metastasis from prostate adenocarcinoma is a rare entity with a low incidence rate (0.36%). Conclusion. Skin metastases, and especially in the scrotum, are exceptional in prostate cancer. However, in any patient with a prostate adenocarcinoma, nonspecific cutaneous lesions should lead to perform skin biopsy in order to identify and initiate treatment of cutaneous metastases.